EFEKTIVITAS JALUR KREDIT DALAM MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA - Regina Mayo; Ghozali Maskie; Devanto Shasta Pratomo (University of Merdeka Malang, 2014)
Transmission mechanism of monetary policy had an important influence in determining the final target ofmonetary policy and also affected the business and economic activity with several channels namely interestrate, asset price channel, credit channel, exchange rate channel and expectations channel. The function ofchanel was as an intermediary of monetary policy that should be able to be influential for a long time, as wellas to anticipate the imperfect information and the possibility of adverse selection and misappropriation. It wasknown as credit channel. The purpose of this research was to explain which sector credit that contributedgreatly to inflation. To analyze data, this research used VECM with two indicators namely impulse responsefunction and variance decomposition to determine which sector credit was effective to explain inflation. Theresults showed several findings. Investment credit of trade, hotel and restaurant sector and working capitalcredit of mining and quarrying sector was effectively explaining inflation. The conclusion of this research wasinvestment credit of trade, hotel and restaurant sector and working capital credit of mining and quarryingsector gave great contribution to inflation